Selective synthesis of Kagome nanoporous graphene on Ag(111) via an organometallic template. Issue 16 (11th April 2022) - Li, Xingyu; Han, Dong; Qin, Tianchen; Xiong, Juanjuan; Huang, Jianmin; Wang, Tao; Ding, Honghe; Hu, Jun; Xu, Qian; Zhu, Junfa
Abstract : We have fabricated Kagome nanoporous graphene potentially exhibiting intriguing properties. The appropriate reaction parameters for improving Kagome networks are determined. Abstract : Kagome nanoporous graphenes (NPGs) are fascinating due to their exotic electronic and magnetic properties. The emerging on-surface synthesis (mostly on metal surfaces) provides a new opportunity to fabricate Kagome NPGs with atomic resolution. Previously the Kagome NPGs synthesized on surfaces were largely heteroatom-doped and suffer from morphological defects (evidently on metal surfaces). The on-surface synthesis of pristine Kagome NPG with improved structural quality is extremely desirable. In this paper, using a halogenated precursor, we report a bottom-up fabrication of pristine NPG with Kagome topology on Ag(111) via classic Ullmann coupling. The templating effect of organometallic (OM) intermediates for subsequent covalent coupling is determined by comparing the OM phase and resultant covalent product. The reaction parameters are found to have a significant impact on the topology and quality of OM intermediates. Specifically, a higher surface temperature and lower evaporation rate favor the growth of better-quality and higher-yield OM Kagome NPGs. The covalent Kagome NPGs obtained by further annealing of these OM networks are affected likewise due to the template effect of OM intermediates. Our work further confirms the generality of the OM template effect. It also offers a novel method to achieve the selective synthesis of Kagome lattice networks.